Improving Interest In Reading Using Assemblr For Young Learners - Hilman; Khaerun; Zein, Suvi Arrivatu; Fajrina, Amia Windy; Rahmawati, Aida; Unzila, Ayu; Solihatunnisa, Putri; Hidayat, Muhammad (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Babunnajah Pandeglang, 2024)
This study aims to provide augmented reality-based learning resources for primary school pupils to enhance their reading comprehension and digital literacy. This study is being conducted in two cycles at SDIT Imam Syafi'i class 5A using the classroom action research (CAR) approach. The findings of the study happened in two cycles: The research tool used observation, questionnaires, tests, and interviews. In the first cycle, the first stage, students did not understand how to use the assemblr application, so they did not understand learning. In the second cycle, students experienced an increase in mastering the assemblr learning media and experienced an increase in reading interest. The study's findings showed that children could read English well, and as a result, they had high enthusiasm for learning to use the Assemblr application.